2018
DOI: 10.1097/bpo.0000000000000875
|View full text |Cite
|
Sign up to set email alerts
|

Graf Type-IV Hips Have a Higher Risk of Residual Acetabular Dysplasia at 1 Year of Age Following Successful Pavlik Harness Treatment for Developmental Hip Dysplasia

Abstract: Level III-therapeutic study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
16
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 24 publications
7
16
0
5
Order By: Relevance
“…Pavlik harness. [33][34][35] We support the conclusion that regular controls are recommended until cessation of growth.…”
Section: Discussionsupporting
confidence: 67%
“…Pavlik harness. [33][34][35] We support the conclusion that regular controls are recommended until cessation of growth.…”
Section: Discussionsupporting
confidence: 67%
“…This difference may be due to the severity of the dysplasia in type-IV hip, compared with type-II and –III hips, with the normal anatomy of the hip being difficult to restore regardless of the type of hip abduction orthosis used. 26 , 30 , 31 Nevertheless, the success rate of THFS for the treatment of Graf type-IV hips appears to be higher than the rate for PH treatment, as previously reported, although we did not compare the THFS with the PH specifically in our study. By comparison, not all type-IV hips treated using the THFS have poor outcomes.…”
Section: Discussionmentioning
confidence: 50%
“… 36 However, Zhou et al 14 indicated that the relatively high incidence of AVN with PH treatment could be attributed to an over-abduction of the hip due to the non-rigid design of the splint. Moreover, Novais et al 30 reported a non-negligible rate of acetabular dysplasia over a one-year period of follow-up in infants with type-IV DDH who had achieved a successful treatment using the PH. In particular, the incidence of residual dysplasia at the six- and 12-month follow-up was 11.7% and 11.8%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it has been shown that early detection of DDHs through a general screening and early treatment are preventive for a large proportion of subsequent extensive hip surgeries [24]. Currently, it is not well understood why a certain percentage of DDH cases that were primarily adequately treated and showed good maturation in sonographic follow-ups have a tendencyindependent of the treatment methodtowards secondary deterioration in radiologic follow-ups at 2 and 5 years [23,25]. It remains a matter of future research whether there is a diagnostic gap after final sonographic control (and impossibility to continue sonography as femoral ossification takes place) and primary radiologic control by a.-p. pelvis X-rays that may not be sensitive enough to diagnose deterioration.…”
Section: Discussionmentioning
confidence: 99%